PENGARUH PEMBELAJARAN BERBASIS LABORATORIUM BERBANTUKAN KIT FISIKA DENGAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR FISIKA SISWA KELAS XI SMAN 8 PADANG - Fatma Adiaty (Universitas Negeri Padang, 2014)
The Physics learning outcome as the standard of mastering learning concept did not reach the minimum passing standard yet. One of the causal factors is the lower rank of interest and motivation which are influenced by the teachers method in delivering Physics learning material. Therefore, the researcher applied the laboratory-based learning with Physics Kit. This research heads for observing the influence of laboratory-based learning with Physics Kit by using Contextual Teaching Learning approach to the Physics learning outcome. The type of this research is a quasi experimental research. The analysis data technique used conversion of score to value, normality test, homogeneity test, and the test of two means comparison. Based on the research outcome, the researcher analyzed the cognitive, affective, and psychomotor domain data. The research outcome showed the working hypothesis, there is a significant influence of laboratory-based learning application with Physics kit by using Contextual Teaching and Learning approach to the Physics learning outcome can be accepted with alpha 0.05